QUESTIONING THE HYBRID MODEL: STUDENT OUTCOMES IN DIFFERENT COURSE FORMATS - Reasons, Saxon G.; Valadares, Kevin; Slavkin, Michael (Online Learning, 2005)
Current literature suggests that a hybrid model of distance education supports student learning more effectively than any other format. It also seems likely that the hybrid format can be used in most courses. The purpose of our study was to examine the strength of these assertions. This study examined the outcomes of two introductory courses in teacher education and health services employing similar pedagogical methods within three delivery formats (face-to-face, internet-based, and hybrid) in an effort to compare each of these modes of instruction. Results demonstrate that significant differences exist among the various formats and that the internet-based format could possibly lead to better student outcomes compared to face-to-face and hybrid formats.